Mathematical modelling of degradation phenomena in organic solar cells under various fabrication conditions - Abdullah, Shahino Mah; Rafique, Saqib; Hamdan, Khairus Syifa; Sulaiman, Khaulah; Taguchi, Dai; Iwamoto, Mitsumasa (Elsevier, 2018)
Lifetime of organic solar cells (OSCs) is much depending on the intrinsic stability of the photoactive layer and its resistance to oxidation process. The encapsulation and the thermal annealing are the known methods to reduce degradation caused due to oxygen ingress which could potentially prolong stability of OSCs. This work is focused on two degradation modes of the photoactive layer: the degradation due to intrinsic material properties and degradation due to oxygen ingress. It is demonstrated that the degradation behaviour of a solar cell can be accurately modelled by using fundamental mathematical equations that describe the aformentioned degradation modes in order to evaluate the lifetime of the solar cells. The case-study of poly[N-9′-heptadecanyl-2,7-carbazole-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole)] (PCDTBT) and (6,6)-Phenyl C71 butyric acid methyl ester (PC71BM) based OSCs has been considered to demonstrate the effectiveness of proposed model for assessing the degradation trends. Our experimental results indicate that temperature annealing has enhanced the stability of OSCs; however, it lowered the efficiency (η) of the OSCs. Further, the numerical results suggest the model of real degradation trends by decaying function with consideration to the possible effects of material deformation (during the burn-in period) and oxidation in photoactive layer of OSCs.